Analisis Hasil Ukur Sensor Arus dan Tegangan untuk Memantau Daya Listrik berbasis Microcontroller - Achlison, Unang; Joseph Teguh Santoso; Khoirur Rozikin; Fujiama Diapoldo (Elkom: Jurnal Elektronika dan Komputer, 2023)
The community's need for electric power is increasing and efforts to monitor electric power are to obtain information on the results of measurements of voltage and electric current. Based on the analysis of the measurement results, it can be concluded that (1) the current measurement is more optimal when using the SCT-013 current sensor, (2) the voltage measurement is more optimal when using the PZEM-004T voltage sensor, (3) the difference in measurements using the current sensor is greater than the difference with a voltage sensor.